Long-term survival and recurrence after curative resection for hepatocellular carcinoma in patients with chronic hepatitis C virus infection: a multicenter observational study from China. Issue 12 (December 2020) - Zhu, Hong; Xing, Hao; Yu, Bin; Yan, Wen-Tao; Zhang, Cheng-Wu; Guan, Ming-Cheng; Zhou, Ya-Hao; Wang, Hong; Zhang, Wan-Guang; Zhang, Yao-Ming; Li, Jie; Wang, Yu; et al.
Abstract: Background: Hepatocellular carcinoma (HCC) is a recognized sequalae of hepatitis B virus (HBV) and hepatitis C virus (HCV) infection. This study aimed to identify long-term survival and prognostic factors after curative resection for HCC among patients with chronic HCV infection. Methods: From a Chinese multicenter database, the data of consecutive patients with HCV infection undergoing curative liver resection for initial HCC between 2006 and 2015 were retrospectively reviewed. Postoperative 30-day mortality and morbidity, long-term overall survival (OS) and recurrence-free survival (RFS) were evaluated. Results: Among 382 HCC patients with HCV infection, 68 (18%) had concurrent HBV infection and 110 (29%) had portal hypertension. Postoperative 30-day morbidity and mortality rates were 45% and 2.9%, respectively. The 5-year OS and RFS rates were 45% and 34%, respectively. Multivariable Cox-regression analyses identified that concurrent HBV infection, presence of portal hypertension, largest tumor size > 5 cm, and macrovascular and microvascular invasion were independently associated with worse OS and RFS, while postoperative regular anti-HCV therapy was independently associated with better OS. Conclusion: Long-term prognosis after HCC resection among patients with HCV infection was worse in those with concurrent HBV infection and concomitant portal hypertension. Postoperative regular anti-HCV therapy was associated with better OS.